Evolutionary origins and diversification of testis-specific short histone H2A variants in mammals - Molaro, Antoine (Genome Res, 2018)
Eukaryotic genomes must accomplish both compact packaging for genome stability and inheritance, as well as accessibility for gene expression. They do so using post-translational modifications of four ancient canonical histone proteins (H2A, H2B, H3, and H4) and by deploying histone variants with specialized chromatin functions. Some histone variants are conserved across all eukaryotes, whereas others are lineage-specific. Here, we performed detailed phylogenomic analyses of “short H2A histone” variants found in mammalian genomes. We discovered a previously undescribed typically-sized H2A variant in monotremes and marsupials, H2A.R, which may represent the common ancestor of the short H2As. We also discovered a novel class of short H2A histone variants in eutherian mammals, H2A.Q. We show that short H2A variants arose on the X Chromosome in the common ancestor of all eutherian mammals and diverged into four evolutionarily distinct clades: H2A.B, H2A.L, H2A.P, and H2A.Q. However, the repertoires of short histone H2A variants vary extensively among eutherian mammals due to lineage-specific gains and losses. Finally, we show that all four short H2As are subject to accelerated rates of protein evolution relative to both canonical and other variant H2A proteins including H2A.R. Our analyses reveal that short H2As are a unique class of testis-restricted histone variants displaying an unprecedented evolutionary dynamism. Based on their X-Chromosomal localization, genetic turnover, and testis-specific expression, we hypothesize that short H2A variants may participate in genetic conflicts involving sex chromosomes during reproduction.